Metal fatigue analysis handbook practical problem-solving techniques for computer-aided engineering - Lee, Yung-Li (Butterworth-Heinemann, 2011)
Understand why fatigue happens and how to model, simulate, design and test for it with this practical, industry-focused reference Written to bridge the technology gap between academia and industry, the Metal Fatigue Analysis Handbook presents state-of-the-art fatigue theories and technologies alongside more commonly used practices, with working examples included to provide an informative, practical, complete toolkit of fatigue analysis. Prepared by an expert team with extensive industrial, research and professorial experience, the book will help you to understand: Critical factors that cause and affect fatigue in the materials and structures relating to your work Load and stress analysis in addition to fatigue damage-the latter being the sole focus of many books on the topic How to design with fatigue in mind to meet durability requirements How to model, simulate and test with different materials in different fatigue scenarios The importance and limitations of different models for cost effective and efficient testing Whilst the book focuses on theories commonly used in the automotive industry, it is also an ideal resource for engineers and analysts in other disciplines such as aerospace engineering, civil engineering, offshore engineering, and industrial engineering. The only book on the market to address state-of-the-art technologies in load, stress and fatigue damage analyses and their application to engineering design for durability Intended to bridge the technology gap between academia and industry-written by an expert team with extensive industrial, research and professorial experience in fatigue analysis and testing An advanced mechanical engineering design handbook focused on the needs of professional engineers within automotive, aerospace and related industrial disciplines.
Keywords: Metals -- Fatigue.; Computer-aided engineering.; elektronické knihy; electronic books